2006
DOI: 10.1190/1.2164759
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic gradient tensor: Its properties and uses in source characterization

Abstract: Airborne magnetic surveys have improved dramatically over the past three decades with advances in both data acquisition and image processing techniques. Magnetic surveys form an integral part of exploration programs and are now routinely undertaken before geological mapping programs. These advances have been made despite treating the magnetic field as a scalar, wherein various processing procedures that assume a potential field are compromised. If the vector information could be retrieved, either by direct mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 0 publications
0
85
0
1
Order By: Relevance
“…Christensen and Rajagopatan (2000) suggested that the next breakthrough in magnetic exploration is likely to be the measurement of the gradient tensor and demonstrated the utility of analytic signal amplitudes (total gradients) of vector components, which can be derived directly from gradient tensor components, for locating boundaries and interpreting source geometries in the presence of remanence. Schmidt and Clark (2006) have summarized the multiple benefits of gradiometry in general and tensor gradiometry in particular.…”
Section: Resource Explorationmentioning
confidence: 99%
“…Christensen and Rajagopatan (2000) suggested that the next breakthrough in magnetic exploration is likely to be the measurement of the gradient tensor and demonstrated the utility of analytic signal amplitudes (total gradients) of vector components, which can be derived directly from gradient tensor components, for locating boundaries and interpreting source geometries in the presence of remanence. Schmidt and Clark (2006) have summarized the multiple benefits of gradiometry in general and tensor gradiometry in particular.…”
Section: Resource Explorationmentioning
confidence: 99%
“…포텐셜에 적용하는 변화율 텐서는 내재적으로 독립 된 성분들의 조합으로부터 이상체의 위치를 가리키는 방향성을 가지고 있다 (Rim, 2011;Schmidt and Clark, 2006 (Blakely, 1996).…”
Section: 서 론unclassified
“…Christensen and Rajagopalan (2000) suggest that the next breakthrough in magnetic exploration is likely to be the measurement of the gradient tensor. Schmidt and Clark (2006) show the properties of the MGT in determining the source characterization.…”
Section: Introductionmentioning
confidence: 99%